On war - Clausewitz, Carl von. (London Wordsworth, 1997)
On War is perhaps the greatest book ever written about war. Carl von Clausewitz, a Prussian soldier, had witnessed at first hand the immense destructive power of the French Revolutionary armies which swept across Europe between 1792 and 1815. His response was to write a comprehensive text covering every aspect of warfare.
Keywords: War